"Wiring" redox-active polyoxometalates to carbon nanotubes using a sonication-driven periodic functionalization strategy. Issue 3 (19th January 2016) - Hu, Jun; Ji, Yuanchun; Chen, Wei; Streb, Carsten; Song, Yu-Fei
Abstract : A universal one-step strategy for the periodic deposition of redox-active polyoxometalate nanocrystals on single-walled carbon nanotubes is reported, giving access to high-performance electrodes for lithium-ion batteries. Abstract : The periodic deposition of redox-active polyoxometalate(POM) nanocrystals on single-walled carbon nanotubes (CNTs) using ultrasonication is reported. The new method allows the controlled formation of 1D POM/CNT nanocomposites where crystals of redox-active POMs of tunable size and shape are deposited at regular intervals on the CNTs. The nanostructure and chemical features of the composite can be tuned through the ultrasonication intensity and time as well as the chemical make-up of the polyoxometalates and their counter-cations. The materials obtained show excellent electrochemical performance as anode materials in lithium-ion- batteries (LIBs) featuring discharge capacities of 850 mA h g −1 for up to 100 cycles.The modular nano-fabrication approach can open new avenues for the bottom-up"wiring" of functional molecular materials to electrically conductive substrates.